A Case of Divine Adultery Investigated - Gaber, Amr.
This paper investigates a corpus of ancient Egyptian documents vis-à-vis the so-called adultery that occurred between Osiris and Nephthys. So far the only account about this story is mentioned by the Greek classical writer Plutarch in his treatise De Iside et Osiride which constitutes part of his work the Moralia as called in Latin in addition to a magical spell found in P. Paris Bibliothèque Nationale Supplement Gr. 574. Moreover, other documents have been perceived as suggesting a relationship between both deities. The main aim of this study is to demonstrate that these documents were taken out of context in order to prove its compatibility with Plutarch’s account. Additionally, other cases that can be seen as divine adultery or reflecting misdeeds of the deities are presented.